2018
DOI: 10.1007/s00396-018-4406-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel block glycopolymers prepared as delivery nanocarriers for controlled release of bortezomib

Abstract: To explore block glycopolymers as novel polymeric delivery nanocarriers for anticancer drug bortezomib (BTZ), three types of block glycopolymers, poly(ethylene glycol)-block-poly(gluconamido ethyl methacrylate) (PEG113-b-PGAMA20), poly(ethylene glycol)-block-poly(styrene)-block-poly(gluconamido ethyl methacrylate) (PEG113-b-PS50-b-PGAMA20), and poly(ethylene glycol)-block-poly(2-(diethyl amino) ethyl methacrylate)-block-poly(gluconamido ethyl methacrylate) (PEG113-b-PDEA50-b-PGAMA20), were synthesized via atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It would, therefore, be conceivable that the structurally less dense SPA to PEGDA (6:4) cryogel microcarriers were able to stockpile more doxorubicin molecules within the core, as compared to the denser SPA to PEGDA (8:2) which only had molecules binding electrostatically to the outer surface of the polymeric network. Previous studies involving doxorubicin and other anticancer drugs have shown similar cases, where of binding affinity of drug to its carrier was found to be influenced by mechanical and, or, chemical properties depending on the accessibility of available functional groups for electrostatic binding (Gagliardi et al 2010;Newland et al 2018;Salgarella et al 2018;Zhang et al 2018b).…”
Section: Doxorubicin Release Studymentioning
confidence: 86%
“…It would, therefore, be conceivable that the structurally less dense SPA to PEGDA (6:4) cryogel microcarriers were able to stockpile more doxorubicin molecules within the core, as compared to the denser SPA to PEGDA (8:2) which only had molecules binding electrostatically to the outer surface of the polymeric network. Previous studies involving doxorubicin and other anticancer drugs have shown similar cases, where of binding affinity of drug to its carrier was found to be influenced by mechanical and, or, chemical properties depending on the accessibility of available functional groups for electrostatic binding (Gagliardi et al 2010;Newland et al 2018;Salgarella et al 2018;Zhang et al 2018b).…”
Section: Doxorubicin Release Studymentioning
confidence: 86%
“…Numerous examples of glycopolymer nanocarriers can be found in the literature based on the described criterion of selective release of the active substance, and several examples are presented in Table 4 , Entries 2, 3, 5–7, 13, 19, 31, 34. [ 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 ]. One example is the nanocarrier PEG-b-PGAMA-b-PDEA ( Table 4 , Entry 6) consisting of poly-(2-(diethylamino)ethyl methacrylate) (PDEA), as a pH-responsive cationic polymer with high biocompatibility, poly(D-gluconamidoethyl methacrylate) (PGAMA) and poly(ethylene glycol) (PEG), the most commonly used hydrophilic segment used in drug delivery systems.…”
Section: Sugar-containing Drug Carriersmentioning
confidence: 99%
“…These glycopolymers have the ability to charge the anticancer drug BTZ to a physiological pH of 7.4 using the conjugation method by the dynamical covalent complexation between glucose and boronic acid, which resulted in the attachment of BTZ to the micelle shell and physical encapsulation by accumulation in the core of micelles as a result of the hydrophobicity of drugs. These glycopolymers, with the ability to self-assemble in micelles, provide a promising polymer nanocarrier system for bortezomib, with extended drug release and accurate controlled release in vivo [ 233 ] .…”
Section: Sugar-containing Drug Carriersmentioning
confidence: 99%
“…42 The pH-responsiveness of tertiary amine-containing polymers is also utilized for drug delivery applications which undergo hydrophobic–hydrophilic switching under an acidic environment. 190,191 Besides the encapsulation by physical interactions, several reports rely on the chemical attachment of drugs with a polymer chain via acid-labile imine linkages and hydrazone. 46,192–194 The presence of a high level of glutathione (GSH) in tumour tissues also motivates researchers to fabricate redox-responsive nanocarriers.…”
Section: Applicationmentioning
confidence: 99%